2013
DOI: 10.1109/te.2012.2219310
|View full text |Cite
|
Sign up to set email alerts
|

Physical Student–Robot Interaction With the ETHZ Haptic Paddle

Abstract: Haptic paddles-low-cost one-degree-of-freedom force feedback devices-have been used with great success at several universities throughout the United States to teach the basic concepts of dynamic systems and physical human-robot interaction (pHRI) to students. The ETHZ haptic paddle was developed for a new pHRI course offered in the undergraduate Mechatronics Focus track of the Mechanical Engineering curriculum at ETH Zurich, Switzerland. Twenty students engaged in this two-hour weekly lecture over the 14 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Haptic paddles have been implemented in multiple senior/graduate level courses, with devices like The Box [10] acting as a plant for embedded controls curriculum. Other paddles adopt a modular approach, either by increasing the degrees of freedom like the Snaptic paddle [11], adding additional sensing such as force sensing or electromyography [12], or altering the haptic paddle plant, such as the series-elastic implementation of the HandsOn-SEA [13] for higher level course objectives.…”
Section: Haptic Paddle Designs and Role In Pedagogymentioning
confidence: 99%
“…Haptic paddles have been implemented in multiple senior/graduate level courses, with devices like The Box [10] acting as a plant for embedded controls curriculum. Other paddles adopt a modular approach, either by increasing the degrees of freedom like the Snaptic paddle [11], adding additional sensing such as force sensing or electromyography [12], or altering the haptic paddle plant, such as the series-elastic implementation of the HandsOn-SEA [13] for higher level course objectives.…”
Section: Haptic Paddle Designs and Role In Pedagogymentioning
confidence: 99%
“…However, the Motors & Music project differs from this project as it focus on dynamic force feedback devices with higher temporal resolution than the ones utilised in this project. Most similar to Motors & Music are projects relating to the Haptic Paddle described in [13], [4] and [16], leading to Stanford's Hapkit [6]. As does Motors & Music, these projects feature educational material aimed at introducing haptics to graduate students.…”
Section: Motivation For the Projectmentioning
confidence: 99%
“…Gassert, et al [17] observed that when objects were used in education as a learning tool, it is evident that the hands-on experience supports higher-order learning; as a result of opportunities for students' to develop their own representations and concepts of educational theories [18]. Furthermore, Gavan & Anderson [4] concluded that the practical application of robotics in undergraduate computing courses in the UK context has been proven to improve student engagement.…”
Section: Introductionmentioning
confidence: 99%